Pengaruh Motivasi Terhadap Efektivitas Kerja di Kantor Camat Tolinggula Kabupaten Gorontalo Utara - Harun, Agriyanti Trisya; Gaffar, Gaffar; Djakaria, Deliana Vitasari; Dunggio, Swastiani (Program Studi Ilmu Pemerintahan, 2024)
Motivation has two basic forms, namely artificial (extrinsic) and intrinsic (intrinsic). Organizations need both in order to improve employee performance. (extrinsic or intrinsic), extrinsic refers to the actions that the organization will take to motivate employees, while intrinsic refers to the forces or causes within the organization that push employees towards certain goals. Because every employee who works certainly has motivation which is the reason why they join the organization of their choice. Based on the results of the researcher's initial observations, work effectiveness at the Tolinggula Subdistrict Office, North Gorontalo Regency is not yet optimal. This can be seen where there are still many public services that cannot be completed on time, simply because the employees serving the public are not there or arrive late to go to the office. Another problem that appears is the slowness of employees in working due to lack of communication. Some employees lack responsibility for their duties and work. If you look at the behavior of employees, it is very clear that employees arrive on time for attendance or roll call in the morning, but after roll call and roll call are finished they do not immediately enter the room and start work, but choose to be quiet and talk to their colleagues and then enter the work room for an hour. after they did attendance and morning assembly. If you assess employees' efforts in carrying out their duties, some employees often delegate their tasks or work to other employees. When appointed by the leadership to carry out work, both inside and outside the office, there are employees who nominate other employees to carry out the task. It was found that the services provided by employees at the Tolinggula Subdistrict Office still showed signs that employee discipline in their work had not been carried out well, this had an impact on employee work results which still showed signs of ineffectiveness in terms of both work quality and time issues. The problem phenomenon above is caused by a lack of motivation for employees. Work effectiveness and employee motivation are closely related; With the support of the right motivation, every employee will try to increase their productivity and have high work morale.